2018
DOI: 10.3390/s18124336
|View full text |Cite
|
Sign up to set email alerts
|

Crack Assessment of Wheel Hubs via an Ultrasonic Transducer and Industrial Robot

Abstract: Crack assessment when making fitness-for-service decisions requires a thorough examination of crack location and size in critical areas. An ultrasonic transducer is used for such assessments, but traditional methods cannot cope with complex rotators, such as wheel hubs. We present a model of robot-assisted crack growth assessment in wheel hubs. We integrate a six-degrees-of-freedom (DOF) industrial robot and a turntable to form a robot-assisted ultrasonic testing (UT) system that does not use traditional UT eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Secanellas [ 8 ] developed a stand-alone synchronization system based on the calculation of post-calibration experiment synchronization mapping and the alignment of the positive mapping, enabling industrial robots to generate high-quality ultrasonic images of the components with complex geometric shapes. Zhang [ 9 ] proposed a robot-assisted wheel crack extension assessment model to quantitatively analyze wheels with a series of longitudinal and transverse pre-cracks. In addition, more research on robotic NDT systems has been carried out by Carmelo Mineo’s team in the UK [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secanellas [ 8 ] developed a stand-alone synchronization system based on the calculation of post-calibration experiment synchronization mapping and the alignment of the positive mapping, enabling industrial robots to generate high-quality ultrasonic images of the components with complex geometric shapes. Zhang [ 9 ] proposed a robot-assisted wheel crack extension assessment model to quantitatively analyze wheels with a series of longitudinal and transverse pre-cracks. In addition, more research on robotic NDT systems has been carried out by Carmelo Mineo’s team in the UK [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The methods are extended by applying distance gain size (DGS) analysis to the output pulse compression signal. The assessment and assessment of cracks [ 19 ] when deciding on suitability for use require an examination of the location and size of cracks in hazardous areas. An ultrasonic transducer is mainly used for such evaluation, but classical methods cannot accurately evaluate the forging, such as mainly wheel hubs.…”
Section: Introductionmentioning
confidence: 99%
“…From his research results, he also showed a method to calibrate the end effector orientation using the ultrasonic alignment method, in order for the robot to adjust the orientation of the tool frame to keep the probe perpendicular to the surface. Further, for large curved rotators, such as wheel hubs, Zhang [6] developed another robot-assisted UT system and in order to improve the inspection sensitivity, the focus depth of the ultrasonic beam was optimized.…”
Section: Introductionmentioning
confidence: 99%